Oligohydraminos in Low Risk Pregnancies at Western Regional Hospital Pokhara - Regmi, Rabi; Singh, Dela; Joshi, Rijuta; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study is done to see the maternal and fetal factors associated with isolated oligohydraminos. Methods: It is a retrospective observational study done at Western Regional Hospital Pokhara. All cases of oligohydraminos except those with diabetes mellitus, hypertension, premature rupture of membranes, preterm labour and fetal congenital anomalies were included in the study. SPSS 16 and MS-Excel were used for data entry and analysis. Results were presented as graphs and tables. Results: Sixty cases were enrolled in the study and the mean age was 25.6 years. Oligohydraminos was more prevalent among primigravida compared to multigravida (62% vs. 38%). Half of the women (n=30) delivered in between 37 to 40 weeks of gestation while 47% (n=28) of the women were post dates and two were post term. LSCS was the most common mode of delivery in this study (n=48). Anhydraminos was detected in seven women (12%) during caesarean section and rest had scanty liquor (41 in LSCS and 12 in vaginal delivery). One fifth of them (n=12) had low birth weight and there were no cases of growth retardation. Eighty two percent of women (n=49) had scanty clear liquor while only seven percent (n=4) had meconium stained scanty liquor. One had stillbirth and the rest had Apgar score of six or more including anhydramnios. Conclusions: There were seven cases of anhydraminos and four cases of meconium stained liquor. All the live births had Apgar score of six or more. There was one stillbirth and neonatal admission each while no neonatal death in this study.